NON LINEAR ANALYSIS OF SCOURING EFFECT TO THE PERFOMANCE OF OFFSHORE PLATFORM STRUCTURE - Purnama A M, Bayu
Nowadays, oil and gas not only explored and exploited on land(onshore), but also in the ocean (offshore). Offshore exploration and exploitation of oil and gas in harder because the technology used is more complicated.supporting infrastructure of offshore exploration and exploitation of oil and gas is called offshore platform. A type of offshore platform commonly used is Jacket Platform. Jacket Platform is an offshore platform used for exploration and exploitation of oil and gas from shallow to medium depth area of the ocean. Platform structure designing mush consider the problems that may accur on the platform structure due to the ocean condition. A common problem at a Jacket Platform is scouring. Scouring is an erosion of ground surface around the Jacket Platform legs which makes somepark of the pile exposed. Scouring occur when the water flow blocked by the platform legs and vortex shedding formed around it. The occurance of scouring is important as it can effect the perfomance and stability structure. This paper show non linear analysis of scoured platform structure. Guidance for this analysis is API RP 2A. Non linear analysis is continuation of the linear analysis as it written in API RP 2A. Non linear analysis showed in the paper is pushover analysis by using USFOS software. This analysis generates reserve strength ratio (RSR) value, pushover graph, and failure trend. To understand the effect of scouring, scouring modelling is done to platform structure with varying vi depths. In this paper, it is up to 10 ft with the scouring depth increasing variably. Besides, platform structure is also modelled to 2 analysis that is in place analysis (operating and storm) and seismic analysis. From the analysis of each scouring depth, sensitivity graph is made by plotting % difference of RSR vs scouring depth and the platform structure’s failure trend is observe for each analysis condition.